Two syntopic new species of the Pristimantis orestes Group (Anura: Strabomantidae) from northwestern Peru - Venegas, Pablo J.; Duellman, William E. (Zootaxa, 2012)
Two new species of Pristimantis (Anura: Strabomantidae), tentatively assigned to the P. orestes Group, are described fromhumid puna (3596 m) of Cañaris, Provincia de Ferreñafe, Región Lambayeque on the eastern slopes of the Cordillera Oc-cidental in northwestern Peru. Pristimantis mariaelenae sp. n. is a medium-sized species characterized by the dorsumvarying from brown to reddish ochre, groin and posterior surface of the thigh with white blotches, pearly white venter withbrown blotches, distinct tympanic annulus and membrane, and tubercles on the eyelid, heel, and outer edge of the tarsus.Pristimantis stipa sp. n. also is a medium-sized species characterized by having narrow discs without marginal grooves, distinct tympanic annulus and membrane present, and Toe III slightly longer than Toe V.